188k views
15 votes
Which quadratic equation is equivalent to (x – 4)2 – (x – 4) – 6 = 0?

(u – 4)2 – (u – 4) – 6 = 0 where u = (x – 4)
u2 – (u – 4) – 6 = 0 where u = (x – 4)
u2 – 16 – u – 6 = 0 where u = (x – 4)
u2 – u – 6 = 0 where u = (x – 4)

User Bjarne
by
5.1k points

2 Answers

6 votes

Answer:

see below.

Explanation:

letting u = x - 4 means the equation can now be expressed as a quadratic

u² - u - 6 = 0 ← quadratic equation in u

User Dmnptr
by
5.0k points
11 votes

Answer: (D)

Step-by-step explanation:

User Zerokavn
by
4.5k points